Pemimpin Transformasional Terhadap Ristensi Perubahan di Masa Pandemi - Putri, Fernanda; Aslami, Nuri (CV. Lafadz Jaya, 2022)
Transformational leaders are leaders who can transform the organization properly so that the goals that have been formulated are achieved. In the current era, the country is being hit by the Covid-19 outbreak which has various impacts on the people of Indonesia. The government's effort to break the chain of spread of the Covid-19 virus is to implement the PSBB and PPKM systems throughout Indonesia. This type of article is written using qualitative research using literature studies. The literature study carried out in writing this article includes analysis and also studies related to books, articles, journals, or other relevant sources that are continuous with the title. The conclusion is that not during the Covid-19 pandemic has a negative impact on people in Indonesia. In terms of leadership, even with a pandemic, it can have a positive influence on the company. This is because leadership can show that it is not as long as a pandemic can hit the world, including the country in Indonesia. In addition, the spirit of leadership can undergo a transformation that there will be a period where it will provide new opportunities for the future.